Contrasting Holocene environmental histories may explain patterns of species richness and rarity in a Central European landscape. (1st February 2016) - Hájek, Michal; Dudová, Lydie; Hájková, Petra; Roleček, Jan; Moutelíková, Jitka; Jamrichová, Eva; Horsák, Michal
Abstract: The south-western part of the White Carpathians (Czech Republic, Slovakia) is known for its exceptional grassland diversity and occurrence of many species with disjunct distribution patterns, including isolated populations of continental forest-steppe species. The north-eastern part of the mountain range lacks many of these species and has clearly lower maxima of grassland species richness. While climatic and edaphic conditions of both regions largely overlap, their specific environmental history has been hypothesized to explain the exceptional richness in the south-western part. We explored an entire-Holocene record (9650 BC onwards), the first one from the north-eastern part, to find out whether differences in history may explain regional patterns of species rarity and richness. We analysed pollen, macrofossils and molluscs and dated the sequence with 13 radiocarbon dates. We further reconstructed past human activities using available archaeological evidence. Based on this analysis, the Early-Holocene landscape was reconstructed as semi-open with broad-leaved trees (elm and lime) appearing already around 9500 BC. Lime reached a relative abundance of as much as 60% around 8700 BC. All analysed proxies support the existence of dense lime-dominated woodland during the forest optimum starting after climate moistening around 6800 BC, some 2200 years before the first signs of slight forest opening in the Late Neolithic. During the Bronze and Iron Ages, human pressure increased, which led to a decrease in lime and an increase in oak, hornbeam, grasses and grassland snails; nevertheless, forests still dominated the landscape and beech spread when human impact temporarily decreased. Colonisation after AD 1350 created the modern grassland-rich landscape. All available evidence confirmed an early post-Glacial expansion of broad-leaved trees, supporting the hypothesis on their glacial refugia in the Carpathians, as well as presence of closed-canopy forest well before the Neolithic. This environmental history was unfavourable for the survival of Early-Holocene forest-steppe species in the north-eastern White Carpathians and may explain the impoverished grassland flora compared to the south-western part. We conclude that contrasting Holocene histories may explain those patterns in species richness and distributions, which cannot be explained by recent environmental conditions alone. Highlights: Holocene development may explain the position of recent biogeographical boundaries. We tested this premise for the flysch region of the White Carpathians (Central Europe). Extremely species-rich meadow-steppe grasslands avoid their northeastern part. We found that a long forest optimum starting before the Neolithic is the reason. Lime was dominant tree, starting already 9500 BC in the pollen record.